Sukavichinomics: Thailand's Preschool and Primary Education Reforms (1995-1997) and Progress Toward Education for All (Global Journal of Human-Social Science, 2025)
Abstract not found
Keywords: sukavichinomics; education reform; early childhood education; Thailand; education for all; 1997 constitution